2016
DOI: 10.1371/journal.pone.0168300
|View full text |Cite
|
Sign up to set email alerts
|

VHDL Descriptions for the FPGA Implementation of PWL-Function-Based Multi-Scroll Chaotic Oscillators

Abstract: Nowadays, chaos generators are an attractive field for research and the challenge is their realization for the development of engineering applications. From more than three decades ago, chaotic oscillators have been designed using discrete electronic devices, very few with integrated circuit technology, and in this work we propose the use of field-programmable gate arrays (FPGAs) for fast prototyping. FPGA-based applications require that one be expert on programming with very-high-speed integrated circuits har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The electronic implementations of these chaotic oscillators were performed herein by exploiting the advantages of the field-programmable gate arrays (FPGAs) for fast prototyping [32]. As already detailed in [33], the mathematical equations modeling a chaotic oscillator can be described through the hardware description language (HDL), which in this work we use the tool Active-HDL. In this manner, the chaotic oscillators are implemented with adders, subtractors and multipliers, as detailed in [32].…”
Section: Fpga-based Implementation Of a Chaotic Secure Communicatiomentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic implementations of these chaotic oscillators were performed herein by exploiting the advantages of the field-programmable gate arrays (FPGAs) for fast prototyping [32]. As already detailed in [33], the mathematical equations modeling a chaotic oscillator can be described through the hardware description language (HDL), which in this work we use the tool Active-HDL. In this manner, the chaotic oscillators are implemented with adders, subtractors and multipliers, as detailed in [32].…”
Section: Fpga-based Implementation Of a Chaotic Secure Communicatiomentioning
confidence: 99%
“…In addition, a PWL function having the forms shown in Fig 1 can be implemented with comparators. The HDL code can be generated according to [33], where it is highlighted that the size of the digital blocks require the number of bits being used, and in this case we use fixed-point notation with format 7.21.…”
Section: Fpga-based Implementation Of a Chaotic Secure Communicatiomentioning
confidence: 99%
“…is important characteristic not only makes FPGAs reusable but also makes them adaptable, extremely cost effective, and perfect choice for prototyping purposes. Furthermore, the design process of the FPGAs, performed by hardware description languages (HDLs), is extremely fast and efficient [38].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of numerical discretization over a chaotic map was recently addressed in [ 3 , 9 , 10 , 11 ]. In our previous work [ 3 ] we have explored the statistical degradation of the phases’ space for a family of 2D quadratic maps.…”
Section: Introductionmentioning
confidence: 99%
“…Nepomuceno et al [ 9 ] reported the existence of more than one pseudo-orbit of continuous chaotic systems when it is discretizated using different schemes. In [ 10 ] and [ 11 ], authors have proposed to use the value of the entropy to choose the number of bits in the fractional part, when maps are implemented in integer arithmetic.…”
Section: Introductionmentioning
confidence: 99%